Downregulated METTL3 Accumulates TERT Expression that Promote the Progression of Ovarian Endometriosis - Fang Li; Hua Tao; Yini Wei; Ru Meng; Yushan Li; Lifang Nie; Yu Zhang; Jinjun Chang (Frontiers in Bioscience-Landmark)
Background: Endometriosis is a complicated and enigmatic disease that significantly diminishes the quality of life for women affected by this condition. Increased levels of human telomerase reverse transcriptase (TERT) mRNA and telomerase activity have been found in the endometrium of these patients. However, the precise function of TERT in endometriosis and the associated biological mechanisms remain poorly understood. Methods: We analyzed TERT expression in ectopic endometrial (EC), eutopic endometrial (EU), and normal endometrial (NC) tissues. Human endometrial stromal cells (HESCs) were used to study the effects of TERT depletion and knockdown on cell behavior. We also assessed methyltransferase-like 3 (METTL3)-mediated N6-methyladenosine (m6A) modification in TERT transcripts and its impact on mRNA stability and cell functions. Results: The current results indicate that TERT expression is elevated in EC tissue compared to both EU and NC. Depletion of TERT suppressed the proliferation and migration of HESCs, while TERT overexpression had the opposite effect. We found high levels of METTL3-mediated m6A modification in TERT transcripts, particularly in the coding sequence region, resulting in increased translation. However, EC tissues had lower m6A levels due to the downregulation of METTL3. Mechanistically, m6A modification mediated by METTL3 negatively regulates the stability of TERT mRNA in a YTH N6-methyladenosine RNA binding protein 2 (YTHDF2)-dependent manner. Furthermore, METTL3 negatively regulated the proliferation and migration of HESCs. Conclusions: Together, our study identified a new molecular mechanism that underlies the pathogenesis of endometriosis. Inhibition of m6A modification and of the METTL3/TERT axis may enhance cellular proliferation and migration, thereby contributing to the progression of endometriosis.